Effect of finishing and polishing on color stability of a nanofilled resin immersed in different media - Oliveira, Ana Luísa Botta Martins De; Lorenzetti, Camila Cruz; Garcia, Patrícia Petromilli Nordi Sasso; Giro, Elisa Maria Aparecida (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
OBJECTIVE:The purpose of this study was to evaluate the effect of finishing and polishing on color stability of a nanofilled composite resin (Filtek Z350 XT) according to different immersion media.MATERIAL AND METHOD:Composite disks (10 mm diameter, 2 mm thickness) were prepared for each group (n = 6) using a stainless steel mold. The groups were divided according to the presence or absence of finishing and polishing procedure and immersion media (artificial saliva, artificial juice- KAPO(r) Coca-Cola(r) flavors: pineapple, orange, strawberry and grape). The finishing and polishing procedures were performed using Super -Snap(r) disks. The specimens were stored in artificial saliva for 24 hours (baseline) and were analyzed using a color spectrophotometer by CIELab system. Then, they were immersed in different media for 5 minutes, 3 times a day, every 4 hours during 60 days. They were stored in artificial saliva at 37 ± 1°C during the immersion intervals. After this time, new measure of color was performed. The data were analyzed using Kruskall-Wallis test and Mann- Whitney test. The significance level was 5%.RESULT:The results showed that the finishing/polishing not significantly influence the color stability of resin composite (p > 0.05). There was no statistically significant difference in the color stability of the studied resin after immersion in different media (p > 0.05).CONCLUSION:The finishing and polishing procedures and the immersion media did not have influence on color stability of nanofilled resin Filtek Z350 XT.

OBJETIVO:O objetivo deste estudo foi avaliar o efeito do acabamento e polimento na estabilidade de cor da resina nanoparticulada Filtek Z350 XT em função de diferentes meios de imersão.MATERIAL E MÉTODO:Espécimes circulares (10 mm de diâmetro e 2 mm de espessura) foram preparados para cada grupo (n=6) utilizando uma matriz de aço inoxidável. Os grupos experimentais foram divididos de acordo com a presença ou ausência de acabamento e polimento e diferentes meios de imersão (saliva artificial, Suco artificial pronto KAPO(r) da Coca Cola(r) sabores: abacaxi, laranja, morango e uva). Os procedimentos de acabamento e polimento foram realizados com discos de lixa Super-Snap(r). Os espécimes permaneceram em saliva artificial por 24 horas (baseline) e foram submetidos à análise da cor usando um espectrofotômetro pelo sistema CIELab. Em seguida, foram imersos nos diferentes meios por 5 minutos, 3 vezes ao dia, com intervalos de 4 horas, durante 60 dias. Os espécimes foram mantidos em saliva artificial a 37±1°C nos intervalos entre as imersões. Após este período foi realizada nova leitura de cor. Os dados foram analisados com os testes de Kruskall-Wallis e Mann-Whitney. O nível de significância foi de 5%.RESULTADO:Os resultados mostraram que o acabamento/polimento não influenciou significativamente a estabilidade de cor da resina composta (p>0,05). Não houve diferença estatisticamente significativa na estabilidade de cor da resina estudada após a imersão nos diferentes meios (p>0,05).CONCLUSÃO:O acabamento e polimento e os meios de imersão não apresentaram influência na estabilidade de cor da resina nanoparticulada Filtek Z350 XT.
Efeito do acabamento e polimento na estabilidade de cor de uma resina composta nanoparticulada imersa em diferentes meios
Keywords: Composite resins; color; dental polishing; Resinas compostas; cor; polimento dental